Impact of Product Quality and Brand Image on Purchase Decision for LGNSHOP Fashion Products - Handayani, Nur; Sutawijaya, Ahmad Hidayat (Jurnal Ilmiah Manajemen Kesatuan, 2024)
This study aims to examine the impact of product quality and brand image on purchasing decisions of LGNShop fashion products, to uses a quantitative method with a survey involving 120 respondents who have used and purchased LGNShop products. The analysis results indicate that product quality and brand image have a positive and significant impact on purchasing decisions. Product quality is assessed based on high-quality materials, attractive designs, and product durability, while brand image is evaluated through effective marketing campaigns and good customer service. This study concludes that improving product quality and managing a good brand image will positively affect consumer purchasing decisions. The implication of this research is that LGNShop needs to continuously improve product quality and maintain a positive brand image to strengthen consumer trust and loyalty.   Keywords: Product Quality, Brand Image, Purchasing Decision, Fashion Products, LGNShop